PENERAPAN STRATEGI INFORMATION SEARCHUNTUK MENINGKATKAN KEMAMPUAN MENULIS KARANGANPADA MATA PELAJARAN BAHASA INDONESIA SISWA KELAS IVSD NEGERI 010 PAGARAN TAPAH DARUSSALAM - Sri Rahayu (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2016)
This research was motivated by the low ability of students in writing essays. The study aims to determine the improvement in essay-writing skills of fourth-grade students of SD Negeri 010 Pagaran Tapah Darussalam through the application of the Strategic Information Search method. The research subjects consisted of 11 students. This study employed classroom action research. The data collection techniques used were observation and essay-writing ability tests. Based on the results, it can be concluded that the application of the Information Search Strategy can improve students’ essay-writing skills in Indonesian language subjects for fourth-grade students of SD Negeri 010 Pagaran Tapah Darussalam. Before the action was taken, students’ essay-writing ability was categorized as “poor,” with an average score of 66.1 and a completeness percentage of 45.45% in the “very low” category. After applying the strategy, improvements were observed in the first cycle, where the class average increased to 73.0, categorized as “fair” (completed). The percentage of completeness achieved in the first cycle reached 72.73%, which falls within the interval of 71–85% in the “medium” category. In the second cycle, the class average increased further to 81, categorized as “good” (completed). In this cycle, students’ completeness in essay-writing skills reached 96.15%, which falls within the 96–100% interval, categorized as “very high.”